Passiflora foetida yielding and nutritional composition - Silva Filho, Danilo Fernandes da; Batista, Manoel Ronaldo Aguiar; Aguiar, Jaime Paiva Lopes; Machado, Francisco Manoares; Figueiredo, José Nilton Rodrigues; Ticona-Benavente, César Augusto (Revista Brasileira de Fruticultura, 2019)
Even though wild maracuja (Passiflora foetida) is cultivated in tropical areas, no thorough investigation regarding its yield or nutritional composition is easily available. This paper aims to estimate its fruit yield, using four staking systems; as well as determine both its fruit pulp and peel chemical composition. The treatments used were T1= No staking, T2= A vertical rod, T3= A horizontal rod, 60 cm from the ground, T4= Two horizontal poles, 60 and 120 cm from the ground, and T5= Using horizontal trellises, 80 cm above ground. The findings showed T5, T4, T3, T2 and T1 to yield 1.40, 1.05, 0.66, 0.40 and 0.35 tons of fruits per hectare, respectively. In general, the fruit pulp held higher nutrient content than that of fruit peel. The pulp presented 2.6%, 4.5% and 24.3% protein, lipids and carbohydrates, respectively. We conclude this genotype to bear low yielding potential, which may be lightly enhanced when cultivated using horizontal trellises. © 2019, Sociedade Brasileira de Fruticultura. All rights reserved.
Composição nutricional e produtividade de Passiflora foetida